If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-6 + -5x) = 68 (-6 * 2 + -5x * 2) = 68 (-12 + -10x) = 68 Solving -12 + -10x = 68 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -10x = 68 + 12 Combine like terms: -12 + 12 = 0 0 + -10x = 68 + 12 -10x = 68 + 12 Combine like terms: 68 + 12 = 80 -10x = 80 Divide each side by '-10'. x = -8 Simplifying x = -8
| 5x+6-x=7+5x-6 | | (X+78)x+42=95 | | 3x+7y=62 | | 3(x+40)= | | (5x-4)(5x+4)=80 | | b-4+2b=27 | | 5-3x=10x-35+2 | | -7(c+372)+620=-185 | | 4(5z+1)-6=178 | | 2(n+7)=5n+8 | | b-4+26=27 | | (X+41)x+78=95 | | 53=29-4(x-4) | | (X+41)+x+78=95 | | 7+2[m-4]=3 | | 90=(3x+13)(5x-7) | | 20%*5000= | | (3x^2+7x-4)+(2x^2-3x-9)= | | 5-9n=31 | | 3h+2h+9=54 | | 13=5x+1-3x | | .20*5000= | | 2975+X(175.75)=5962.72 | | 9+-5x=12+-1(6x+7) | | 0.3(4x-2)=-0.8x+9.4 | | 2c^2+9c+10=0 | | 6000-1240= | | (X+41)+95=x+78 | | 2x+9-x=9+2x-6 | | 74=8(c+4)-4 | | 4760/45= | | 2.5=3.7-0.4x |